(untitled) (Scientific journal of the Fergana State University, 2024)
The article scientifically describes the medicinal value, chemical composition and medicinal properties of the Taraxacum officinale plant. It plays an important role in maintaining human and societal health. Bioactive substances such as alkaloids, tannins, flavonoids and phenolic compounds contribute to the medicinal properties of the plant. Information is provided about its important role in medicine, folk medicine, the chemical composition of the plant, medicinal properties, and analysis of its chemical components.